2014
DOI: 10.1186/s12941-014-0037-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-Listeria potentials of some plant-derived triterpenes

Abstract: BackgroundListeriosis is a fatal disease caused by pathogenic Listeria bacteria and it is most prevalent in immune-compromised individuals. The increase in numbers of immune-compromised individuals against a background of Listeria antibiotic resistance, limits listeriosis treatment options. This therefore calls for research into substitute treatments, of which, medicinal plants derived compounds offer a viable alternative.MethodsThe broth microdilution assay was used to determine the minimum inhibitory concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
1
8
1
1
Order By: Relevance
“…The combined results of the present and previous (Penduka et al, 2014;Mosa et al, 2014b) studies support the postulations that the mode of action of triterpenoids is not yet fully understood (Chung et al, 2011). This then leads to the possible conclusion that the triterpenes work on multiple target sites, such that their mechanism of action is possibly a combination of the blockage of cell division through DNA synthesis inhibition and the inhibition of macromolecular synthesis which may also be linked to cell membrane damage (de Leon and Moujir, 2008).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The combined results of the present and previous (Penduka et al, 2014;Mosa et al, 2014b) studies support the postulations that the mode of action of triterpenoids is not yet fully understood (Chung et al, 2011). This then leads to the possible conclusion that the triterpenes work on multiple target sites, such that their mechanism of action is possibly a combination of the blockage of cell division through DNA synthesis inhibition and the inhibition of macromolecular synthesis which may also be linked to cell membrane damage (de Leon and Moujir, 2008).…”
Section: Discussionmentioning
confidence: 76%
“…However, previous antibacterial studies on RA3 and RA5 by Penduka et al (2014) and Mosa et al (2014b) showed some MIC values within the ranges of 100-1000 µg/ml. Interestingly, the study by Mosa et al (2014b) similarly proved RA3 and RA5 to having a high MIC value of above 1000 µg/ml against E. coli bacteria.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In recent years, the medicinal values of pentacyclic triterpenoids have been increasingly recognized and studied because of their anti-inflammatory [39], hypoglycemic [1,30], antibacterial [40,41], antioxidant [42,43], antitumor [44][45][46], antiproliferative [47], anti-HIV [48][49][50], antitrypanosomal [51], antileishmanial [52,53], anti-arthritic [54], hepatoprotective [55,56], cardiovascular [57], and immunological adjuvant [58] activities. In the past decade, numerous reports indicated that pentacyclic triterpenoids exhibit various bioactivities.…”
Section: Introductionmentioning
confidence: 99%